Gender, HIV knowledge and prevention attitudes among adolescents living with HIV participating in an economic empowerment intervention in Uganda. Issue 7 (3rd July 2021) - Nabunya, Proscovia; Byansi, William; Muwanga, Joelynn; Damulira, Christopher; Brathwaite, Rachel; Namuwonge, Flavia; Bahar, Ozge Sensoy; Ssewamala, Fred M.
ABSTRACT: HIV disproportionately affect adolescent girls and young women in sub-Saharan Africa. In Uganda, the HIV prevalence is four times higher in adolescent girls compared to boys. This study examined gender, HIV general and clinical knowledge, and prevention attitudes among adolescents living with HIV in Uganda. Data from a cluster randomized clinical trial were analyzed. A total of 702 adolescents (average age of 12.4) were randomized to either a control arm receiving bolstered standard of care or the treatment arm receiving bolstered standard of care plus a family economic empowerment intervention to support medication adherence. Ordinary Least Squares models that adjust for clustering of adolescents within health clinics were conducted. No gender differences were observed in HIV knowledge and prevention attitudes at baseline. However, at 12-months follow-up, boys were more likely than girls to report correct HIV general knowledge (d  = 0.21), clinical knowledge ( d  = 0.48), and favorable prevention attitudes ( d  = 0.27). The intervention was not associated with any of the outcomes. Given the high HIV prevalence among adolescents, specifically girls, there is need to develop and/or tailor existing programs and interventions that equip adolescent girls with comprehensive knowledge and prevention attitudes, that are culturally appropriate, to reduce HIV transmission and reinfection within this population.